Child Guardianship from the Perspective of Islamic Family Law: A Study of Padangsidimpuan Religious Court Case No. 150/Pdt.P/2024/Pa.Psp - Yunita Pasaribu; Ibrahim Siregar; Putra Halomoan Hasibuan; Zeti Isra Tri Oktafia .Z (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The appointment of a guardian for a child in the context of Islamic family law in Indonesia, particularly in case Number 150/Pdt.P/2024/PA.Psp at the Religious Court of Padangsidimpuan, reflects the interaction between positive law provisions and Islamic legal principles. This study aims to analyze the judge's considerations in determining the child's guardian, from juridical, sociological, and normative Islamic perspectives. The research methodology used is a qualitative approach with a case study. The results show that the judge's considerations are based on the authority of the religious court, the status of the child who is not yet of legal age, and the eligibility of the proposed guardian in accordance with the provisions in the Compilation of Islamic Law (KHI). The judge also takes into account the principle of the best interest of the child and the child’s welfare in appointing a guardian. The decision is based on a thorough analysis of the lineage, moral and social capacity of the petitioner, as well as the condition of the child residing in an orphanage. Moreover, the study identifies challenges faced by the court in the implementation of guardianship, particularly regarding the role of local government in the supervision and revocation of guardianship. Overall, this research shows that the appointment of a guardian in the Religious Court of Padangsidimpuan integrates Islamic family law principles with social realities while ensuring the protection of the child’s rights in guardianship matters.